Spatial distribution of pathogenic fungal isolates from clinical samples in Uganda: Diagnostic gaps and trends, January 2020 - May 2024. - Priscilla Atim; Samuel Gidudu; Bernard Ssentalo Bagaya; Andrew Kambugu; Grace Najjuka; Atuhaire D Winfred; Benedict Kanamwanji; Esther Nabende; Adella Atukunda; Jonathan Kabazzi; Sylvia Joyoo; Hildah Tendo Nansikombi; et al. (PLoS ONE)
Background Pathogenic fungi cause approximately 13 million infections and 1.5 million deaths worldwide each year, yet surveillance and diagnosis remain inadequate in resource-limited settings. In Uganda, fungal infections affect approximately 4,099,357 per 45 million people annually, resulting in severe invasive diseases if untreated. This study describes laboratory-confirmed pathogenic fungal isolates from clinical samples in Uganda from January 2020 to May 2024, and highlights gaps in diagnostic capacity. Methods We abstracted data from the National Microbiology Reference Laboratory database, disaggregated pathogenic fungal isolates by the sex and age group of the patients, sample type, and isolated species, district, and year of isolation. Pathogenic fungal isolates were confirmed by culture and biochemical tests. Using Epi Info 7 software, we analyzed frequencies. Results Among 8,136 clinical samples tested, fungal pathogens were isolated from 744 (9%) samples. Of these, the majority were obtained from female (92%), persons aged 16-35 years (68%). Most fungal pathogens (93.7%) were isolated from superficial clinical samples, while 6.3% from deep samples. High-vaginal swabs accounted for 71% of the clinical samples, with most cases from Kampala (32%) and Mbarara (26%) districts. The pathogenic fungal species identified included C. albicans (65.4%), non-albicans Candida spp. (30.6%) and C. neoformans (3.9%). We observed a sharp decline of identified pathogenic fungi from 299 (40%) in 2020-39 (5%) in 2024, reflecting diagnostic disruptions during the COVID-19 pandemic. Conclusion Candida spp. were the most commonly isolated pathogenic fungi, mainly among females and individuals aged 16-35 years from Kampala and Mbarara districts. There is need for targeted interventions against candidiasis in these groups and locations. This study also highlights the gaps in fungal diagnostic capacity in Uganda, as the national database was limited to Candida and Cryptococcus, emphasizing the need for improved diagnostic infrastructure, capacity-building and surveillance to enhance detection of pathogenic fungi.